2013
DOI: 10.1515/ntrev-2012-0084
|View full text |Cite
|
Sign up to set email alerts
|

PLA/PLGA nanoparticles for delivery of drugs across the blood-brain barrier

Abstract: Abstract:The blood-brain barrier (BBB), which protects the central nervous system (CNS) from unnecessary substances, is a challenging obstacle in the treatment of CNS disease. Many therapeutic agents such as hydrophilic and macromolecular drugs cannot overcome the BBB. One promising solution is the employment of polymeric nanoparticles (NPs) such as poly (lactic-co-glycolic acid) (PLGA) NPs as drug carrier. Over the past few years, significant breakthroughs have been made in developing suitable PLGA and poly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 43 publications
(172 reference statements)
4
28
0
Order By: Relevance
“…We also tested QDs-loaded PLGA particles (PLGA 3-QD) to identify how zeta potential affects cellular uptake of particles. The behavior of cellular uptake assessed by fluorescence microscopy and flow cytometry indicated that the uptake of FPN 3-QD was inferior to that of PLGA 3-QD which is possibly correlated with the higher degree of negative zeta potential and hydrophilicity of FPN 3-DTX [53,54]. Without DTX drug loading, it was found that FPN-3 displayed high biocompatibility in the absence of DTX compared to the PLGA-3.…”
Section: Discussionmentioning
confidence: 97%
“…We also tested QDs-loaded PLGA particles (PLGA 3-QD) to identify how zeta potential affects cellular uptake of particles. The behavior of cellular uptake assessed by fluorescence microscopy and flow cytometry indicated that the uptake of FPN 3-QD was inferior to that of PLGA 3-QD which is possibly correlated with the higher degree of negative zeta potential and hydrophilicity of FPN 3-DTX [53,54]. Without DTX drug loading, it was found that FPN-3 displayed high biocompatibility in the absence of DTX compared to the PLGA-3.…”
Section: Discussionmentioning
confidence: 97%
“…Different strategies, such as the use of nanotechnology, have emerged to tackle these problems. In general, nanoparticles-based drug delivery systems present important advantages, such as a long lifetime circulation, ability to improve the drug’s aqueous solubility as well the bioavailability, and the capacity to overcome physiological barriers [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained NPs were first characterized and compared to control empty NPs, both with and without PEI. All NPs produced showed hydrodynamic diameter ranging from 230 to 280 nm (Table 1), which is suitable for potential in vivo applications [34,35,36], and indicates that the presence of PEI and BSA does not affect the outcome of nanoprecipitation in terms of size. Conversely, PEI strongly affects the surface charge of NPs and leads to cationic NPs, as expected.…”
Section: Resultsmentioning
confidence: 99%